Prevalence of significant anxiety symptoms and associated factors among adult people with HIV/AIDS in care and treatment clinic centers in Kilimanjaro region, Tanzania: a cross-sectional study - Frank Kiwango; Eric Mboya; Florian Emanuel Ghaimo; Neema Ng’unda; Carl Mhina; Editruda Gamassa; Kim Madundo; Ester Steven Mzilangwe; Lyidia Vedasto Masika; Iddi Haruna; Saidi Bakari Kuganda; Blandina Mmbaga; et al. (BMC Psychiatry)
Background People with human immunodeficiency virus (PWH) are more prone to generalized anxiety disorder. There is a limited understanding of the prevalence of significant anxiety symptoms and its associated risk factors among adult PWH in the Tanzanian context. This study aims to determine the prevalence of significant anxiety symptoms and related risk factors among adult PWH attending care and treatment clinics in Moshi Municipality, Kilimanjaro Region. Methods We used a multistage random cluster sampling approach to select participants at four Care and treatment centers (CTCs) of Kilimanjaro Christian Medical Centre, Mawenzi Regional Referral Hospital, Majengo, and Pasua Health Centre, by location at tertiary, secondary, and primary health care levels. The seven-item Generalized Anxiety Disorder (GAD-7) screening tool assessed levels of generalized anxiety symptoms with significance set at scores ≥ 10. Sociodemographic, clinical, and psychosocial characteristics were collected using a semi-structured questionnaire. Bivariate analyses determined factors associated with significant anxiety symptoms (GAD-7 ≥ 10) at p-values $$\:\le\:$$ 0.20 for inclusion in the multivariate model. Adjusted prevalence ratios with confidence intervals are reported with significance set at a p-value of < 0.05. Results Out of 593 PWH participants, 12.48% screened positive for significant anxiety symptoms. Participants treated at the tertiary health facility level (aPR = 2.91, 95% CI: 2.48–3.41, P-value = 0.001), early adulthood 25–44 years (aPR = 1.75, 95% CI: 1.27–2.42, P-value = 0.001), with higher anxiety sensitivity (aPR = 3.28, 95% CI: 2.08–5.19, P-value = 0.001), and higher levels of perceived social support (aPR = 2.09; 95% CI: 1.34–3.27, P-value = 0.001) showed a higher likelihood of significant generalized anxiety symptoms. Conclusions Significant anxiety symptoms were common among adult PWH. Integrating routine generalized anxiety screening and raising PWH’s and primary caregivers’ awareness of GAD is recommended. Trial registration Clinical trial number not applicable.